2021
DOI: 10.1021/acs.accounts.1c00038
|View full text |Cite
|
Sign up to set email alerts
|

Design of Abiological Digital Poly(phosphodiester)s

Abstract: Conspectus In biological systems, the storage and transfer of genetic information rely on sequence-controlled nucleic acids such as DNA and RNA. It has been realized for quite some time that this property is not only crucial for life but could also be very useful in human applications. For instance, DNA has been actively investigated as a digital storage medium over the past decade. Indeed, the “hard-disk of life” is an obvious choice and a highly optimized material for storing data. Through decades of nucleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 62 publications
(172 reference statements)
2
52
0
Order By: Relevance
“…Inspired by the biological functions arising from the well-defined chemical structures of biopolymers, the synthesis of polymers without molecular weight distribution and sequence uncertainty has been pursued extensively in polymer chemistry. The synthesis of monodisperse polymers has relied mostly on the sequential addition of individual monomers via solid-phase synthesis. However, with the increase in molecular weight or number of repeating units, their synthesis becomes difficult, which limits the availability of monodisperse polymers and the study of their properties. Recent developments of synthetic strategies including the iterative exponential growth and the cross-convergent synthesis have allowed the synthesis of high-molecular-weight monodisperse polymers with defined sequences. These advances have provided the opportunities to study the behavior of synthetic polymers with defined sequences and the absence of structural uncertainty. Furthermore, monodisperse and sequence-defined polymers offer the opportunity to explore unprecedented applications of polymeric materials owing to the precisely defined chemical and physical properties dictated by their chemical structures. …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the biological functions arising from the well-defined chemical structures of biopolymers, the synthesis of polymers without molecular weight distribution and sequence uncertainty has been pursued extensively in polymer chemistry. The synthesis of monodisperse polymers has relied mostly on the sequential addition of individual monomers via solid-phase synthesis. However, with the increase in molecular weight or number of repeating units, their synthesis becomes difficult, which limits the availability of monodisperse polymers and the study of their properties. Recent developments of synthetic strategies including the iterative exponential growth and the cross-convergent synthesis have allowed the synthesis of high-molecular-weight monodisperse polymers with defined sequences. These advances have provided the opportunities to study the behavior of synthetic polymers with defined sequences and the absence of structural uncertainty. Furthermore, monodisperse and sequence-defined polymers offer the opportunity to explore unprecedented applications of polymeric materials owing to the precisely defined chemical and physical properties dictated by their chemical structures. …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been recently demonstrated that this chemistry can also be used to prepare sequence-defined synthetic polymers. [88][89][90] Thus, iterative phosphoramidite chemistry is not only the gold standard method for DNA synthesis but also an interesting polymer chemistry tool. 91 Since this method can be applied to both phosphoramidite nucleosides and non-natural phosphoramidite monomers, it is a very convenient platform for the synthesis of bio-hybrid macromolecules containing both synthetic and DNA segments.…”
Section: Phosphoramidite Polymer Chemistrymentioning
confidence: 99%
“…They all contain a main-chain nitrogen atom and alkyl side-chain substituents of increasing size, namely methyl (M1), propyl (M2), pentyl (M3) and heptyl (M4). Following our laboratory convention, 19 monomers of increasing molar mass M1, M2, M3 and M4 represent binary dyads 00, 01, 10 and 11, respectively. Main-chain propyl spacers were intentionally placed between oxygen and nitrogen atoms in all these monomers.…”
Section: Chart 1 Molecular Structure Of the Monomers Prepared And Use...mentioning
confidence: 99%
“…tandem mass spectrometry, MS/MS), racemic synthons can be used to construct them. For instance, our group has reported the synthesis of digital poly(phosphodiester)s (d-PPDE), [17][18][19] in which a comonomer alphabet is used to write binary information. 20 These polymers are prepared by solid-phase phosphoramidite polymer chemistry (PPC); a versatile method that can be used for synthesis of biological (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation